A gestão dos estoques de materiais na administração pública - Carvalho, Conceição Sousa Vidal (2009)
Stocks represents significative costs to the organizations. Into the public organizations, stock control of material can to contribute a lot to upgrade of the public resources. The question is, how works the stock control of materials in the warehouse of public administration. This dissertation intends verifying the stock control of materials in the warehouse of public administration of Bahia State, identifying appropriate parameters to this kind of management, specificilly, examining the stock control of materials in the warehouse of public administration of Bahia State. The methodologic strategy used was based on a couple of stages: first one is the behavior approach and the second one is the empiric study. On behavior approach, are developped the logistics concepts, supply, re-supply and stock control. The empiric study, has a information search the Warehouse Inspection Project, performed between 04/07/2007 at 31/10/2007, by the Secretaria da Administração (SAEB), towards Superintendência de Serviços Administrativos (SSA), into the 61 warehouses belonging at the 41 management units linked to the Governement of Bahia State. Among this 61 warehouses used on the Project, was choosed a warehouse from a management unit, called RS Warehouse Unit (this name was created to preserve the real name). This choice was justified because the management unit use all the modules of the State system, called Integrated Material, Shareholder and Service System (SIMPAS). Either to be an unit with high costs about consumer goods of stock. Among the result finded, show it off: 622 item above the maximum stock, 957 item below of minimum stock, 961 item below of reorder level and 190 item without handling. That means a total of fixed capital by R$ 227.026,86. The RS Unit don t use methods like just-in-time, ABC classification and critical ratio. The warehousing area is dirty, dusty and exposed to humidity. There is storage on the floor, item without label and right localization. The materials selected of to the inventory, all showed up phisic and financial differences. This dissertation concludes that the RS Unit doesn t get an efficient and efficacious management able to reduce the public costs and make the upgrade of resources in the public administration.